Parent-initiated Health and Education Services for Children with Autism in Baguio, Philippines - Gattud, Vincent Isilen; Piduca, Michael Joel Canilang (Indonesian Journal of Disability Studies, 2020)
Autism requires individualized services to maximize full and effective participation in society. Legal mandates facilitate coordination of health and education services for children with autism. Descriptive correlation was utilized to describe the health and education services initiated by the parents of children with autism in an urban locality in the Philippines, which has no legal framework for services specific to them. Likert-type questionnaires gathered data from purposively sampled respondents. There is selective utilization of health and education services for children with autism. The parent's number of children, income, and level of education significantly varied how they perceived educational programs and health services. Different aspects of educational services correlated with the availed health services. Accessibility and availability of health and educational services must be improved. Study more on health and education services’ impact on children with disabilities at different levels of education and health care system.